Social media contributions toward service quality of the academic libraries / Wan Nor Haliza Wan Mokhtar ... [et al.] - Wan Mokhtar, Wan Nor Haliza; Hussin, Norhayati; Muhammad Hashim, Nurulain Najwa; Ibrahim, Zaharudin; Hashim, Hasnah; Abu Bakar, Amzari (Faculty of Information Management, 2023)
This paper is discussing on the social media contributions toward service quality of the academic libraries. Everyone aware that social media has become an operative information distribution tool which involves minimal effort in order to be operated by libraries for marketing their informational resources and cultural efforts. Social media is now considered as an emerging occurrence in giving overview about a product. Not only to business, but librarians nowadays recognized the significance of social media in the libraries and information centres. Despite of lack of allocation on budget and resources, librarians still need to strive to meet up with the anticipation of their users in terms of providing their ever-changing needs. With the fact that there are abundances of information which is easily accessible on the internet, libraries should optimize the power of social media in order to give room for interactive communication with the library users and public in an online environment. Furthermore, social media has the potential of improving the image of the library and improving the users experience. The use of social media in library address greater library promotion programs, engaging and increased involvement of the users in library activities besides enhancing the library community building. The objective of this study is mainly to determine the reliability of social media toward service quality in libraries. A quantitative approach was employed in both data collection and data analysis. The study population is made up of the students of the Universiti Teknologi MARA (UiTM) Selangor.